2017
DOI: 10.1037/a0040147
|View full text |Cite
|
Sign up to set email alerts
|

Age and health jointly moderate the influence of flexible work arrangements on work engagement: Evidence from two empirical studies.

Abstract: Research and theory support the notion that flexible work arrangements (i.e., job resources in the form of formal policies that allow employees the latitude to manage when, where, and how they work) can have a positive influence on various outcomes that are valued both by organizations and their constituents. In the present study, we integrate propositions from various theoretical perspectives to investigate how flexible work arrangements influence work engagement. Then, in 2 studies we test this association a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 124 publications
1
37
0
5
Order By: Relevance
“…Across literatures, a great deal of effort has been invested to properly estimate the independent influence of age, period, and cohort (APC) effects (e.g., Baltes, 1968;Costanza & Finkelstein, 2015;Costanza, Darrow, Yost, & Severt, 2017;Hofer & Sliwinski, 2006;Koslowski, 1986;Schaie, 1986;Yang, 2008;Yang & Land, 2013). For example, research has looked at the effect of age as a marker of individual development in the work context (e.g., Rudolph & Baltes, 2016), of major historical events on various populations (e.g., Elder, 1974;Elder & Liker, 1982), and on differences among cohorts (e.g., Gerstorf, Ram, Hoppmann, Willis, & Schaie, 2011;Schaie, 2013). However, in most of these studies, age, period, and cohort are not independent of each other and, hence, separating out their relative effects is challenging, if not impossible.…”
Section: Cross-temporal Meta-analysis: a Conceptual And Empirical Crimentioning
confidence: 99%
“…Across literatures, a great deal of effort has been invested to properly estimate the independent influence of age, period, and cohort (APC) effects (e.g., Baltes, 1968;Costanza & Finkelstein, 2015;Costanza, Darrow, Yost, & Severt, 2017;Hofer & Sliwinski, 2006;Koslowski, 1986;Schaie, 1986;Yang, 2008;Yang & Land, 2013). For example, research has looked at the effect of age as a marker of individual development in the work context (e.g., Rudolph & Baltes, 2016), of major historical events on various populations (e.g., Elder, 1974;Elder & Liker, 1982), and on differences among cohorts (e.g., Gerstorf, Ram, Hoppmann, Willis, & Schaie, 2011;Schaie, 2013). However, in most of these studies, age, period, and cohort are not independent of each other and, hence, separating out their relative effects is challenging, if not impossible.…”
Section: Cross-temporal Meta-analysis: a Conceptual And Empirical Crimentioning
confidence: 99%
“…There are elements in job design to build-in autonomy to enhance PWB (Park & Searcy, 2012), such as flexible working arrangements (FWA). FWA not only increases job autonomy, but it can also increases work life balance (WLB) (Rudolph & Baltes, 2017) and therefore PWB (Boreham et al, 2016). However, other research revealed that FWA could lead to insecurity (Lange, 2013), with some scholars identifying more nuanced relationship necessitating FWA/WLB practices that need to be coupled with effective team design in order to be effective (Liu & Wang, 2011).…”
Section: Paradoxical Pwb Practicesmentioning
confidence: 99%
“…(Karimi, Cheng, Bartram, Leggat, & Sarkeshik, 2015), while van Mierlo et al (2006 found that practices that stimulate learning mitigate the effects of work intensification. L&D practices that stimulate individuals through task design can reduce emotional exhaustion and thereby increase PWB (Rudolph & Baltes, 2017).…”
Section: Mutual Gains Pwb-performance Practicesmentioning
confidence: 99%
“…This paper extends existing literature by examining how a particular antecedent − work-family conflictinfluences the formation and evolution of employee job embeddedness and demonstrating how work-family conflict is an antecedent of aspects of employee job embeddedness. Third, despite the predictive powers of workplace flexibility, little is understood about its role as a moderator (Rudolph & Baltes, 2017). In this study, we examined whether workplace flexibility moderates the effect of work-family conflict on employee turnover intention.…”
Section: Resultsmentioning
confidence: 99%